2009
DOI: 10.1016/j.jcrs.2009.07.009
|View full text |Cite
|
Sign up to set email alerts
|

Dry eyes and corneal sensation after laser in situ keratomileusis with femtosecond laser flap creation

Abstract: Keywords Femtosecond · Laser in situ keratomileusis · Suction loss · Narrow palpebral fissure · Flap creation Abstract Purpose: To evaluate a surgical technique used in eyes with narrow palpebral fissure undergoing femtosecond laser flap creation without suction during laser in situ keratomileusis (LASIK). Methods: All data of 2 patient groups were collected through chart review. Group 1 consisted of 6 eyes with narrow palpebral fissure in which the suction ring was manually fix-ated and femtosecond laser was … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
57
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 72 publications
(62 citation statements)
references
References 30 publications
5
57
0
Order By: Relevance
“…There was no difference in corneal sensation between the different hinge positions, angles, or flap thicknesses at any time point. This study also showed that dry-eye syndrome after LASIK with a femtosecond laser was mild and improved after 3 months (Mian et al, 2009). …”
Section: Complicationssupporting
confidence: 53%
“…There was no difference in corneal sensation between the different hinge positions, angles, or flap thicknesses at any time point. This study also showed that dry-eye syndrome after LASIK with a femtosecond laser was mild and improved after 3 months (Mian et al, 2009). …”
Section: Complicationssupporting
confidence: 53%
“…Furthermore, regarding whether or not differences in tear menisci parameters exist between the microkeratome and femtosecond laser methods of flap formation, between different types of femtosecond lasers, and the possible effects of corneal flap hinge location and hinge angles, future investigations are warranted. 45 In summary, LASIK significantly decreased the upper and lower tear menisci after surgery, and recovery of the lower tear menisci took place over a period of 1 week to 3 months. There were no significant differences in the tear meniscus parameters with regard to flap creation by microkeratome or femtosecond laser.…”
Section: Discussionmentioning
confidence: 80%
“…The nervous system regulates logarithmically the inter-blink interval in a symmetrical manner. This characteristic seems to be invariable and it would be interesting to determine whether the inter-blink time intervals also follow a Log Normal distribution in the presence of conditions that affect blink rate such as psychosis (13) , Parkinson's disease (5) , sleep deprivation (14) , drug use (8) , and dry eye, as well as the rates induced by refractive surgery such as LASIK (15) . …”
Section: Discussionmentioning
confidence: 99%